The Effect of Changes in the Political Climate on Intercountry Trade: An Econometric Analysis on Turkey-Russia Aircraft Crisis - Can, Esin; Ozmutlu, Saniye Yildirim; Aykac, Cansu (ISTANBUL UNIV, 2019)
The core components of the political environment are ideological climate and political processes, nationalism, interventions of governments and political stability. The effects of these changes on international trade are accepted reality in terms of scientific community, countries, and businesses. For this reason, the aim of this paper is to investigate the effect of the political crisis between Turkey and the Russian Federation after the airplane crises on November 24, 2015. Thus, the effect of commercial relations between the two countries by linking variables has been shown in a quantitative study. The study has three parts. In the first part, we look at the political risk concept and political and commercial relations. In the second part of the study, the political crisis is the independent variable and control variables are the CPI-based real effective exchange rate, the monthly percentage change in the CPI and industrial production index. The Turkey-Russia trade volume is considered as the dependent variable. We analyzed the effect of the political crisis on foreign trade volume within the scope of these variables. In order to show the effect of political relations on the foreign trade volume between Turkey and the Russian Federation, a time series regression analysis was conducted with the STATA program. In addition, changes in foreign trade volume were explained with charts obtained by digitization of the Turkey Statistics Institute (TUIK) and the Central Bank (MB) reports. As a result of these analyses, it is concluded that the political crisis has had a meaningful and a negative effect on foreign trade volume. In other words, the reality in the literature is examined by studying a concrete case. In the last part of the study, the results obtained were evaluated and recommendations were made.
Keywords: Political risk; Commercial relations; Turkey-Russian Federation; Foreign trade; RISK; Government & Law